Utilization of Social Media by Young Initiators of Religious Harmony in Strengthening Religious Moderation: Pemanfaatan Media Sosial Inisiator Muda Kerukunan umat Beragama dalam Penguatan Moderrasi Beragama - Sulvinajayanti, Sulvinajayanti; Islam, Nidaul; Arsil, Muh; Qurota Ayun, Silmi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Religious moderation is key to the creation of tolerance and aggression at various levels. In Indonesia, building a community among diverse societies is a priority for the Ministry of Religion. South Sulawesi, with a majority of its population Muslims, has a dynamic of harmonious religious life without serious interreligious conflict. This devotional activity aims to increase the involvement of cross-religious youth as agents of change in strengthening religious moderation and gatherings through social media. The implementation of the activities is carried out with the community-based research (CBR) approach, which covers the four stages of policy-making, planning, data collection and analysis, and action on findings. These stages include training, focus group discussions, and the establishment of a cross-religious youth institution active in social media. The activities resulted in two major achievements, namely the creation of the Interreligious Youth Foundation in Kelurahan Amparita, known as the Three One Village, and the publication of crowd content in the form of photos, videos, and messages disseminated through social media and the website https://sipakatabe.id/. This dedication program successfully consolidated the concept of brotherhood as a foundation for interreligious gatherings in the Sidrap district. Young pioneers of the crowd gain knowledge in the creation of crowd content and actively engage in the dissemination of tolerant messages. This program is expected to be a model for other regions in building a congregation of religious people. The recommendation of the Ministry of Religious Affairs of Sidrap District is to continue building the young generation through the Village Development Programme. (PDSKUB).